KONSTRUKSI BERPIKIR MENYELESAIKAN MASALAH OPERASI PECAHAN PADA MATEMATIKA KONTEKSTUAL DENGAN KERANGKA POLYA - Rahayuningsih, Sri; Kristiawan, Indria (FKIP Universitas Wisnuwardhana, 2018)
The purpose of this study is to describe the construction of student thinking in solving contextual mathematical problems with a framework of patterns. The importance of constructing student thinking in learning contextual mathematics is so that mathematics learning does not lose meaning and is expected to improve mathematics teaching in schools. This study uses qualitative methods and the subjects in this study are selected based on the results of the solution, namely: students with the results of completion and answers correctly referred to as M1, students with incorrect results but answers are correct as M2, and students with correct completion and wrong answers as M3. The three subjects were asked to solve the problem of contextual mathematical fraction operations with a framework of patterns. Construction of thinking in solving fractions in contextual mathematics experienced by the subject is a construct based on mental structure. This is indicated by the existence of several activities, namely (i) solving questions based on prior knowledge (Action); (ii) reflect on the results of the settlement (Process); (iii) explain the outcome of the settlement and at the same time be able to give an example (Object); and (iv) design and complete mathematical models that have been formed by using actions, processes, objects, and other schemes of a problem related to fractions (Scheme).Keywords:Â construction thinking, problem solving, fractional operations, contextual mathematics